Self-Reported Knowledge and Awareness of Musician-Related Disorders Among Music Educators and Pre-Service Music Teachers in Higher Education Institutions in Türkiye: An Occupational Health Literacy Perspective - Rıza Akyürek; Ayşe Şevval Dinçer (Healthcare, 2026)
Background/Objectives: Musicians face occupational health risks from repetitive movement, sustained posture, and intensive practice. This study examined self-reported knowledge of musician-related disorders, physical complaints, and selected health practices among music educators and pre-service music teachers, using occupational health literacy (OHL) as an interpretive framework. Methods: A cross-sectional survey included 432 participants from public higher education institutions in Türkiye (83 educators; 349 pre-service teachers). The primary outcome was a common 15-item self-reported disorder knowledge score (range 15–75). Psychometric and nonparametric analyses included effect sizes, confidence intervals, and multiplicity correction. Results: Instrument-related physical problems were reported by 49.4% of educators and 53.0% of pre-service teachers. After false discovery rate correction, hand/wrist complaints were more frequent among pre-service teachers. The score showed a one-factor structure and excellent internal consistency. Educators (n = 79; M = 38.73, SD = 14.71) scored higher than pre-service teachers (n = 341; M = 26.81, SD = 12.35; U = 20,062.0, p < 0.001; rank biserial r = 0.489, 95% CI 0.364–0.602). Conclusions: Knowledge was uneven, especially for specialized conditions. Targeted musician-health education, communication, and referral pathways are warranted. The score is not a comprehensive OHL measure or a test of clinical competence, and causal effects on preventive behavior or occupational well-being cannot be inferred.